A Virtual Reality Application for the Rehabilitation of Children with Cerebral Palsy - Mendes, Diego Caracas; Rodrigues, Edson Coelho; Farias, Emanuel Bandeira; Barbosa, Ícaro; Gomes, George A. M.; Cavalcante Neto, Joaquim Bento; Vidal, Creto Augusto; Leite Junior, Antonio J. M. (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
The development of virtual environments to support rehabilitation for various diseases and special needs has gained significant attention in recent years. These environments offer numerous advantages for patients and healthcare professionals, including increased motivation and engagement among patients and the possibility of objective and personalized monitoring of the rehabilitation process for professionals. These benefits become even more relevant when the target audience is children, considering the difficulties related to concentration and understanding of the situation by such young patients, as well as the psychological and emotional burden that clinical environments often impose on minors. This paper presents the development and evaluation of an immersive VR application designed to support physical therapy in pediatric patients. Built in collaboration with physiotherapists, the system employs a “slideshow” metaphor to guide children through interactive narratives within a tropical forest environment. The solution prioritizes simplicity of use for professionals and engagement for young users while enabling therapists to observe and stimulate cervical and cognitive functions. Initial testing with children aged 3 to 17 revealed positive responses, particularly in cervical movement stimulation and interaction quality, although cognitive abilities significantly influenced engagement. The results demonstrate the potential of VR as an effective and adaptable therapeutic aid, paving the way for future expansions, allowing flexible creation of different narratives, and also targeting other diverse neuropsychomotor conditions.